Tomato Prenylated RAB Acceptor Protein 1 Modulates Trafficking and Degradation of the Pattern Recognition Receptor LeEIX2, Affecting the Innate Immune Response - Pizarro, Lorena; Leibman-Markus, Meirav; Schuster, Silvia; Bar, Maya; Meltz, Tal; Avni, Adi (Frontiers in Plant Science, 2018)
Plants recognize microbial/pathogen associated molecular patterns (MAMP/PAMP) through pattern recognition receptors (PRRs) triggering an immune response against pathogen progression. MAMP/PAMP triggered immune response requires PRR endocytosis and trafficking for proper deployment. LeEIX2 is a well-known S. lycopersicum RLP-PRR, able to recognize and respond to the fungal MAMP/PAMP EIX, and its function is highly dependent on intracellular trafficking. Identifying protein machinery components regulating LeEIX2 intracellular trafficking is crucial to our understanding of LeEIX2 mediated immune responses. In this work, we identified a novel trafficking protein, SlPRA1A, a predicted regulator of RAB, as an interactor of LeEIX2. Overexpression of SlPRA1A strongly decreases LeEIX2 endosomal localization, as well as LeEIX2 protein levels. Accordingly, the innate immune responses to EIX are markedly reduced by SlPRA1A overexpression, presumably due to a decreased LeEIX2 availability. Studies into the role of SlPRA1A in LeEIX2 trafficking revealed that LeEIX2 localization in multivesicular bodies/late endosomes is augmented by SlPRA1A. Furthermore, inhibiting vacuolar function prevents the LeEIX2 protein level reduction mediated by SlPRA1A, suggesting that SlPRA1A may redirect LeEIX2 trafficking to the vacuole for degradation. Interestingly, SlPRA1A overexpression reduces the amount of several RLP-PRRs, but does not affect the protein level of receptor-like kinase PRRs, suggesting a specific role of SlPRA1A in RLP-PRR trafficking and degradation.